Proximity effects on nuclear spin-spin coupling constants. 1. 1J(CH) couplings in the vicinity of an atom bearing lone pairs - Vizioli, C. (1994)
Proximity effects on 1J(CH) couplings are studied from a theoretical point of view in the following systems: CH4/FH (A) and H2O/HCN (B) which form dimers by hydrogen-bond interactions. 1J(CH) couplings for different intermolecular distances are calculated for the C - H bond facing the atom bearing lone pairs. While in the former system, this coupling is increased owing to the proximity to the F atom; in the latter this coupling is decreased owing to the proximity to the O atom. These opposite trends are accompanied by slight shortening and lengthening, respectively, of the corresponding C - H bond lengths. As part of this work, measurements of 1J(CH) couplings in 9-(1,3-dioxolan-2-yl)-1,2,3,4-tetrafluorotriptycene (I) and 1-formyl-2-hydroxy-8-fluoronaphthalene (II) and 1J(NH) in o-fluorobenzamide (III), showing proximity effects as those described above are carried out. These results suggest that 1J(XH) couplings are adequate probes to distinguish two different types of X-H⋯Y hydrogen bonds. © 1994 American Chemical Society.